Effectiveness of solid waste management systems in local government authorities in Tanzania: The case of Moshi municipal council - Khamis, Amina A (Mzumbe University, 2024)
A thesis submitted to the School of Public Administration and Management in partial fulfillment for the requirements of the award of degree of Master of Public Administration (MPA) of Mzumbe University, Tanzania